A step towards personalizing next line therapy for resected pancreatic and related cancer patients: A single institution's experience. (June 2020) - Lowder, Cinthya Y.; Dhir, Teena; Goetz, Austin B.; Thomsett, Henry L.; Bender, Joseph; Tatarian, Talar; Madhavan, Subha; Petricoin, Emanuel F.; Blais, Edik; Lavu, Harish; Winter, Jordan M.; Posey, James; et al.
Abstract: Background: There is a lack of precision medicine in pancreatic ductal adenocarcinoma (PDA) and related cancers, and outcomes for patients with this diagnosis remain poor despite decades of research investigating this disease. Therefore, it is necessary to explore novel therapeutic options for these patients who may benefit from personalized therapies. Objective: Molecular profiling of hepatopancreaticobiliary malignancies at our institution, including but not limited to PDA, was initiated to assess the feasibility of incorporating molecular profiling results into patient oncological therapy planning. Methods: All eligible patients from Thomas Jefferson University (TJU) with hepatopancreaticobiliary tumors including PDA, who agreed to molecular testing profiling, were prospectively enrolled in a registry study from December 2014 to September 2017 and their tumor samples were tested to identify molecular markers that can be used to guide therapy options in the future. Next generation sequencing (NGS) and protein expression in tumor samples were tested at CLIA-certified laboratories. Prospective clinicopathologic data were extracted from medical records and compiled in a de-identified fashion. Results: Seventy eight (78) patients were enrolled in the study, which included 65/78 patients with PDA (local and metastatic) and out of that subset, 52/65 patients had surgically resected PDA. Therapy recommendations were generated based on molecular and clinicopathologic data for all enrolled patients. NGS uncovered actionable alterations in 25/52 surgically resected PDAs (48%) which could be used to guide therapy options in the future. High expression of three proteins, TS (p = 0.005), ERCC1 (p = 0.001), and PD-1 (p = 0.04), was associated with reduced recurrence-free survival (RFS), while TP53 mutations were correlated with longer RFS (p = 0.01). Conclusions: The goal of this study was to implement a stepwise strategy to identify and profile resected PDAs at our institution. Consistent with previous studies, approximately half of patients with resected PDA harbor actionable mutations with possible targeted therapeutic implications. Ongoing studies will determine the clinical value of identifying these mutations in patients with resected PDA. Highlights: How precision medicine can be used in PDA. Highlighting the use of NGS and protein expression in PDA tumor samples. NGS uncovered actionable alterations in 48% of resected PDAs (48%). NGS can be used to guide therapy options in the future. High levels of TS, ERCC1, and PD-1 proteins were associated with decreased in RFS.